Application of floyd's algorithm on transport network of south bohemian region - Hanzl, Jiří; Bartuška, Ladislav; Rozhanskaya, Elena; Průša, Petr (My University, 2016)
The introductory part of the paper deals with the theory of searching for optimal routes in transport networks, including a description of each type of optimization tasks. The aim of the article is demonstration of Floyd algorithm application to find the minimal paths from each node to another in network graph - in our case the network represents traffic model of road network in the region of South Bohemia.
Aplikace Floydova algoritmu na dopravní síť Jihočeského kraje
Keywords: distance matrix; traffic network; transport model; Floyd algorithm; optimal route; minimal path; matice vzdáleností; dopravní síť; dopravní model; Floydův algoritmus; optimální trasa; minimální cesta